2010 IEEE/RSJ International Conference on Intelligent Robots and Systems 2010
DOI: 10.1109/iros.2010.5650879
|View full text |Cite
|
Sign up to set email alerts
|

Parts assembly by throwing manipulation with a one-joint arm

Abstract: The present paper proposes the learning control method for the throwing manipulation which can control not only the position but also the orientation of the polygonal object more accurately and robustly by low-degree-of-freedom robotic arm. We show experimentally the validity of the proposed control method with the one-degree-freedom robotic arm. We also demonstrate the usefulness of the throwing manipulation by applying it to sorting task and assembly task on experiments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…A throwing model with simple kinematics including an air drag influence was presented in [6]. Miyashita et al [7], [8] suggested a control strategy for a 1-DoF rotational robot with edges based on iteration optimization learning. For this purpose a nonlinear optimization problem is solved by the sequential quadratic programming (SQP) method for different initial conditions with constraints on actuator limits and final object position.…”
Section: Introductionmentioning
confidence: 99%
“…A throwing model with simple kinematics including an air drag influence was presented in [6]. Miyashita et al [7], [8] suggested a control strategy for a 1-DoF rotational robot with edges based on iteration optimization learning. For this purpose a nonlinear optimization problem is solved by the sequential quadratic programming (SQP) method for different initial conditions with constraints on actuator limits and final object position.…”
Section: Introductionmentioning
confidence: 99%